A One‐Off Wealth Levy? Assessing the Pros and Cons and the Importance of Credibility*. (23rd December 2015) - Kempkes, Gerhard; Stähler, Nikolai
Abstract: From an economic perspective, imposing a credibly one‐off net wealth levy in times of crisis as a tool to ward off a national emergency appears to be advantageous as, in an ideal world, this would not distort market players' allocation decisions. However, in practice, charging such a levy may give rise to distortions and unwanted effects on the real economy. Credibility that the levy will be imposed as a once‐only measure is key to ensuring that harmful distortions in the allocation of resources are kept to a minimum. This paper confirms this using an analysis based on a dynamic stochastic general equilibrium (DSGE) model. In practice, while a government cannot guarantee that such a measure will be taken once only, it can contribute to the credibility of this in a number of ways. First, the country's future 'business model' must become apparent; second, there has to be a basic level of confidence in the government and a firm belief that the budgetary imbalances were not actively caused by the state – at least not by the government currently in power; third, a verifiable outlook of sustainable public finances must be in place; and fourth, the political costs of a repeat levy must be high. This paper also discusses the potential impact of alternative model set‐ups as well as some practical implementation problems.